2018
DOI: 10.5552/drind.2018.1743
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Examination and Modification of Chip Suction System in Circular Sawing Machine

Abstract: The article presents the results of experimental examination of the wood chip suction system in the existing sliding table saw before and after its modifi cation. The studies focused on the extraction hood of the mentioned system. The methodical experimental research of the pressure distribution inside the hood during wood chip removal for the selected rotational speed of saw blades of 3500 and 6000 min-1 with a diameter of 300 mm and 450 mm were carried out. The analysis of the results allowed estimating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The size of the obtained particles when drilling without a proper suction system might pose a potential risk to the health of woodworkers. The results are similar when considering sawing operations [5] and the milling process in [6]. Moreover, cutting parameters impact the dust emission and the surface quality during wood machining [7], [8].…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…The size of the obtained particles when drilling without a proper suction system might pose a potential risk to the health of woodworkers. The results are similar when considering sawing operations [5] and the milling process in [6]. Moreover, cutting parameters impact the dust emission and the surface quality during wood machining [7], [8].…”
Section: Introductionmentioning
confidence: 76%
“…Wood manufacturing operations emit air pollutants and dust particles. When not properly removed, dust particles can cause problems in the machining systems: damage and immediate loss of performance [1]. Breathing dust particles also increases the risk of nasal cavity cancer and lung cancer among workers with cumulative exposure [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to determining the correct rotational speed of the tool and the feed per tooth or chip thickness, appropriate construction and assembly of the upper suction hood is also required. Studies of Barański et al [30], Barański and Pikała [31], and Barański et al [32] indicate that improving the design of the upper suction hood can be an effective factor in improving the efficiency of dust extraction from circular saws. In addition, Mikkelsen et al [33] claim that bad design of the exhaust hood is frequently the reason for increasing dust concentration near woodworking machine.…”
Section: Resultsmentioning
confidence: 99%
“…Engineering controls Proper use of dust extraction systems is regarded as the most important technical workplace control ] demonstrated that the use of main and auxiliary sawdust extraction connectors together ensured the highest reduction in wood dust exposures to 0.5 mg/m 3 during sawing activities. Baranski et al [49] and Cui et al [25] showed that correct design of the upper suction hood for dust extraction from circular saws, and the correct positioning of dust collecting hoods can improve the efficiency of dust removal. Furthermore, optimizing cutting parameters and the location of operators in relation to these machines can contribute to reducing the spatial distribution of MDF dust levels.…”
Section: Workplace Control Measures To Reduce Exposuresmentioning
confidence: 99%